Theoretical analysis on the elasticity of a novel accordion cellular honeycomb core with in-plane curved beams. (March 2020) - Liu, Weidong; Li, Honglin; Zhang, Jiong; Li, Hongda
Abstract: Flexible skin is an essential component for morphing wind turbine blade to maintain a smooth profile and bear aerodynamic loads during morphing. Cellular honeycomb cores with low in-plane and high out-of-plane stiffness are potential candidates for support structures of flexible skin. Honeycomb structure also requires zero Poisson's ratio to avoid unnecessary stress and strain during one-dimensional morphing. A novel accordion cellular honeycomb core of close-to-zero Poisson's ratio with in-plane corrugated U-type beams was proposed as a solution for these problems. The elastic properties of the structure are illustrated through a combination of theoretical analysis and finite element analysis. Results show that better in-plane morphing and out-of-plane load-bearing capabilities can be obtained with parameters of larger height-to-length ratio, spacing-to-length ratio and vertical beam to U-type beam thickness ratio as well as smaller thickness-to-length ratio. Results of comparisons on properties of the proposed honeycomb with two existing accordion honeycombs reveal that the in-plane elastic modulus of the proposed structure is as low as about 56% of that of the accordion honeycomb with V-type beams and 79% of that of the accordion honeycomb with cosine beams, showing better in-plane property but weaker out-of-plane load-bearing capability. Nevertheless, the out-of-plane load-bearing capability can be reinforced by increasing the vertical beam to U-type beam thickness ratio. Smaller driving force and less energy consumption are required by the proposed honeycomb core than conventional structures during morphing. The methods and results could be used for predictions of elasticity in design of sandwich morphing skin with similar cellular honeycomb cores.